From Sacrifice to Sacrament: A Christocentric Theology of the Cross Justifying the Sacramental Status of Protestant Marriage - Lahadinirina Lucien Hajatiana; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR-Publisher), 2025)
Marriage largely remains excluded from the acknowledged list of sacraments within Reformed Protestantism. This historical posture stems from sixteenth-century doctrinal controversies where Reformers, notably Luther and Calvin, redefined the concept of sacrament, limiting it to the two rites explicitly instituted by Christ : Baptism and the Lord’s Supper. Nevertheless, contemporary theologians have increasingly challenged this exclusion, arguing that marriage, as a divinely willed and blessed union, merits reintegration into a revitalized understanding of sacramentality. Protestant scholars have proposed sophisticated models for inclusion, often relying on a Trinitarian and Christocentric interpretation of the conjugal mystery. This study adopts a distinct approach, centering reflection on the Cross of Christ and His earthly ministry as the supreme revelation of Divine Love. Employing the hermeneutical insights of Paul Ricœur and the dogmatic structure of Karl Barth, the investigation explores how Christ's sacrificial love profoundly grounds a theology where marriage functions as a visible sign of Grace and a genuine locus of Divine Presence. The argument hinges specifically on the theological density of John 3:16 and the Christological mandate of Ephesians 5:25. It has been demonstrated that, through a theology of the Cross centered on the incarnational ministry of Jesus, Christian marriage is legitimately recommended as a sacrament within the Reformed context. Matrimony embodies a dynamic of self-giving, redemption, and Trinitarian communion, perfectly mirroring the covenantal union between Christ and the Church. The doctrines of Solus Christus and Christus in medio serve to underscore the implicit sacramental character of marriage: it is an act rooted in biblical Revelation and the Divine Will. Ultimately, the sacramental revaluation of marriage affirms its triple dimension : it manifests the image of God, His presence, and the fulfillment of His salvific will in the daily experience of the faithful. Through a new Theology of the Cross focused on the broken Body of Jesus Christ, this thesis advocates for the sacramentality of Protestant marriage—a position faithful to the spirit of the Reformation yet enriched by a profound, contemporary reading of Revelation. Marriage is thereby established as an essential channel of grace, a primary space for sanctification, and a living testimony of Christian faith.